Selenium-Binding Protein 1 (SELENBP1) as Biomarker for Adverse Clinical Outcome After Traumatic Spinal Cord Injury - Seelig, Julian; Heller, Raban Arved; Haubruck, Patrick; Sun, Qian; Klingenberg, Georg Jochen; Hackler, Julian; Crowell, Helena Lucia; Daniel, Volker; Moghaddam, Arash; Schomburg, Lutz; Biglari, Bahram (Frontiers in Neuroscience, 2021)
INTRODUCTION: Traumatic spinal cord injury (TSCI) presents a diagnostic challenge as it may have dramatic consequences for the affected patient. Additional biomarkers are needed for improved care and personalized therapy. OBJECTIVE: Serum selenium binding protein 1 (SELENBP1) has been detected in myocardial infarction, reflecting hypoxic tissue damage and recovery odds. As SELENBP1 is usually not detected in the serum of healthy subjects, we tested the hypothesis that it may become detectable in TSCI and indicate tissue damage and regeneration odds. METHODS: In this prospective observational study, patients with comparable injuries were allocated to three groups; vertebral body fractures without neurological impairment (control “C”), TSCI without remission (“G0”), and TSCI with signs of remission (“G1”). Consecutive serum samples were available from different time points and analysed for SELENBP1 by sandwich immunoassay, for trace elements by X-ray fluorescence and for cytokines by multiplex immunoassays. RESULTS: Serum SELENBP1 was elevated at admission in relation to the degree of neurological impairment (graded as A, B, C or D according to the American Spinal Injury Association (AISA) impairment scale (AIS)). Patients with the most severe neurological impairment (classified as AIS A) exhibited the highest SELENBP1 concentrations (p=0.011). During the first three days, SELENBP1 levels differed between G0 and G1 (p = 0.019), and dynamics of SELENBP1 correlated to monocyte chemoattractant protein 1, chemokine ligand 3 and zinc concentrations. CONCLUSION: Circulating SELENBP1 concentrations are related to the degree of neurological impairment in TSCI and provide remission odds information. The tight correlation of SELENBP1 with CCL2 levels provides a novel link between Se metabolism and immune cell activation, with potential relevance for neurological damage and regeneration processes, respectively.